Phytochemical and Biological Study on Plants (F. Aizoaceae) - Haggag, Eman G.; Youssif, Khayrya A.; Gabr, Nagwan M.; Rabeh, Mohamed A.; Elshamy, Ali M. (Current Overview on Pharmaceutical Science Vol. 6, 2023)
The Aizoaceae is one of the greatest succulent plant families. Most members of the family are ornamental plants and form part of specialist succulent collections. The Aizoaceae family has exceptional diversity, especially in its many traditional uses. Certain species are well known in folk medicines, with recent scientific studies validating their biological activity. The purpose of this research is to provide a comprehensive review of the phytochemical constituents and biological activities of plants in the Aizoaceae family (Mesembryanthemaceae). The study includes articles from 1969 to 2018, reviewed from internationally recognised databases, as well as scientific data from scientific journals. Phytochemical studies of plants in the Aizoaceae family have revealed the presence of a variety of compounds, including alkaloids, triterpenes, sterols, lignans, phenolic compounds, betacyanins, and essential oils. Studies on the biological properties of plants in the Aizoaceae family have revealed a wide range of bioactive potentials, including antioxidant, anti-diabetic, anti-microbial, anti-tumor, hepatoprotective, and other benefits. The described medicinal plants of the Aizoaceae family were chosen and compiled based on their biological activities and phytochemical components. The findings of this review article stimulate additional ethnobotanical and ethnopharmacological studies and investigations into the quest for new drugs.